Long term results of pneumatic retinopexy - Ellakwa AF (Dove Medical Press, 2012)
Amin F EllakwaMenoufiya University, Shibin el Kom, Al-Menoufiya, EgyptBackground: Rhegmatogenous retinal detachment is a commonly encountered retinal problem where rapid treatment can prevent irreversible vision loss. Pneumatic retinopexy (PR) is a simple, minimally invasive procedure for retinal reattachment.Purpose: This study aimed to assess the long-term anatomical and functional outcome of pneumatic retinopexy in primary rhegmatogenous retinal detachment.Patients and methods: A prospective interventional study was performed. Subjects with rhegmatogenous retinal detachment who underwent pneumatic retinopexy from May 2006 to May 2007 at Menoufiya University Hospital were included in this study with at least 3 years follow-up.Results: A total of 40 cases were included in the study. The mean age of patients was 44.25 ± 10.85 years. Reattachment of the retina was achieved in 100% of cases. In 75% of cases, the primary intervention was successful. However, the retina redetached in 20% of these during the first 6 months, requiring reinjection or another procedure. Three years after the first intervention, follow-up measurement of the mean visual acuity of the eyes without reoperation was 0.40 ± 0.21 while the mean visual acuity of the eyes which needed additional operations was 0.22 ± 0.13.Conclusion: Sixty percent of the cases obtained long-term retinal reattachment with a single operation success (SOS), with good visual recovery and less morbidity than other more invasive procedures like scleral buckling or pars plana vitrectomy, translating to higher productivity for the patient. This procedure, being quicker than the alternatives, also saves the surgeon's time, making PR a good choice for managing primary rhegmatogenous retinal detachment in developing countries.Keywords: pneumatic, retinopexy, rhegmatogenous, retinal detachment